The Effect of Nine Facets of Job Satisfaction for Creative Employees in Creative Agency - Sumedho, Sumedho (iBuss Management, 2015)
The goal of this research is to find if Nine Facets of Job Satisfaction by Spector (1997) can explain job satisfaction for creative employee in Creative Agency. This research is inspired by the conclusions from The Orange Economy by Howkins and Indonesiaâs Long-Term Development Plan 2005-2025 by the Ministry of Tourism and Creative Economy that creative economy has unlimited growth possibilities. The author is interested to find what exactly satisfies creative employees for future improvements in Creative Agency. Binary logistic regression is used to analyze the significance/insignificance of Nine Facets of Job Satisfaction to predict job satisfaction of creative employees. The research subjects are the population of creative employees in Creative Agency, which are 37 in total. Result of this research shows that Nine Facets of Job Satisfaction as a whole can predict job satisfaction of creative employee inÂ  Creative Agency, but not individually. Â Keywords: Creative employee, Nine Facets of Job Satisfaction, Job Satisfaction, Binary logistic regression